Pelaksanaan Analisis Beban Kerja Pada Jabatan Pelaksana di Sub Bagian Kelembagaan dan Analisis Jabatan Bagian Organisasi Sekretariat Daerah Kota Surabaya - Afianti, Nur Azizah; Gading Gamaputra (Universitas Negeri Surabaya, 2023)
Workload analysis is a management activity aimed at determining the level of proportionality of positions. This research sees problems in the preparation stage of forming an internal team experience gaps with the training criteria in the guidelines, as well as a mismatch between position requirements and existing employees. The method used is descriptive with the focus of research on the stafes of implementing workload analysis based on Perka BKN No. 10 of 2021 consists of preparation, data collection, data processing, and verification and validation of calculation results. The results of research in the field show that preparation is carried out through application preparation planning, team formation consists of two levels and the internal team experiences gaps in the quality aspects of training with criteria, organizational assessment based on job descriptions, unit notification, and submission of forms carried out through socialization meetings. Data collection applies to the whole method. Data processing uses the calculation of tasks per position task with the results of the calculation of 1 employee of the Head of Subdivision of Institutional and Job Analysis, 4 employees of Position Analysts, 1 employee of Institutional Analysts, and 4 employees of Organizational and Procedural Data Managers. However, the calculation results experienced gaps, this was motivated by the fact that the position map only describes existing civil servants, the accumulation of employee needs has not been rounded, and the impact of the implementation of the moratorium policy. Verification and validation of calculations are carried out by issuing a decision letter. Suggestions submitted by researchers are to conduct training planning through the preparation of position competency standard documents, standardize the time of executive positions based on clumps, fulfill employees through recruitment of non-civil servants, coordinate with the position in charge of applications to improve the rounding system in calculating employee needs according to applicable regulations.